Kanji and non-homophonous furigana: Foreign language readings and character (stereo)types in manga. (December 2019) - Redmond, Ryan C.
Abstract: The present study seeks to investigate how one manga series Bleach, by Tite Kubo, uses a language-specific process to employ loanwords as tools to invoke a stereotype injection, as well as index certain character traits without overt characterization through dialogue. I argue in this paper that the Japanese writing system offers a key mechanism for this indexing. The system traditionally encompasses three different character sets: kanji (characters originally borrowed from/based off of the Chinese writing system), hiragana (a moraic script used for native and functional words), and katakana (a moraic script used for foreign words, sound effects, etc.). These sets each have their own normatively specialized usages, and because of this, they have come to index certain social stereotypes. One aspect of Japanese writing which may also be associated with stereotypes that has been less studied is furigana . Traditionally written in hiragana or katakana, furigana are annotations serving a metalingual function, and are primarily used to give the pronunciations of unknown or obscure kanji that the reader might not recognize. A less-frequently employed secondary purpose is giving a non-standard reading to a kanji character or series of characters. What has not received direct attention yet is how furigana itself can be used to index certain social or cultural stereotypes. While past research has looked at furigana in manga, few of these have looked at systematic uses of non-Japanese furigana readings. Through analysis of the usage of Spanish-derived and German-derived furigana readings in Bleach, it was determined that the origin language of the furigana word often correlates with a certain character type, and functions as a way to inject stereotypes about characters into even small portions of their dialogue. Further, it was determined that many of the social stereotypes concerning these languages were present in word choice and kanji usage, yielding a cultural idea of characterological type without the need for overt characterization, which is helpful in dealing with Bleach 's large cast of named characters.